Wenxin Keli for the Treatment of Arrhythmia—Systems Pharmacology and In Vivo Pharmacological Assessment - Li, Xiaofeng; Tian, Gang; Xu, Liang; Sun, Lili; Tao, Rui; Zhang, Shaoqiang; Cong, Zidong; Deng, Fangjun; Chen, Jinhong; Yu, Yang; Du, Wuxun; Zhao, Hucheng (Frontiers in Pharmacology, 2021)
This study employed a systems pharmacology approach to identify the active compounds and action mechanisms of Wenxin Keli for arrhythmia treatment. Sixty-eight components identified in vivo and in vitro by UPLC/Q-TOF-MS were considered the potential active components of Wenxin Keli. Network pharmacology further revealed 33 key targets and 75 KEGG pathways as possible pathways and targets involved in WK-mediated treatment, with the CaMKⅡ/CNCA1C/Ca2+ pathway being the most significantly affected. This finding was validated using an AC‑induced rat arrhythmias model. Pretreatment with Wenxin Keli reduced the malignant arrhythmias and shortened RR, PR, and the QT interval. Wenxin Keli exerted some antiarrhythmic effects by inhibiting p-CaMKⅡ and intracellular Ca2+ transients and overexpressing CNCA1C. Thus, suppressing SR Ca2+ release and maintaining intracellular Ca2+ balance may be the primary mechanism of Wenxin Keli against arrhythmia. In view of the significance of CaMKII and NCX identified in this experiment, we suggest that CaMKII and NCX are essential targets for treating arrhythmias.